Protection for Women as A Response of Pregnancy prior to Marriage Phenomenon in Bali - Ni Komang Ratih kumala Dewi; Ni Luh Gede Yogi Arthani; Ni Komang Sutrisni; Putu Putri Pradnyani Dewi; Ni Nyoman Dewi Mega Purnami Sari (University of Udayana, 2023)
The development of sing beling sing nganten (pro-choice for married by accident) the sing beling sing nganten phenomenon in Bali is causing concern among parents and the community due to the younger generation's inclination towards engaging in sexual relationships before marriage, often with the intention of pregnancy. Various triggering factors lead them to these actions. Women, in particular, may not fully contemplate the repercussions or considerations if their plans go awry. Consequently, there's a need for protective measures for women within this phenomenon. The research aimed to identify the necessary protection for women in response to this phenomenon. Employing empirical and legal research methods, the study utilized oral data from interviews and direct observation of real behaviors. The research identified two forms of protection for women concerning this phenomenon: Preventive Legal Protection and Repressive Legal Protection.